Clean and healthy living behaviors are associated with hypertension prevention and control: A systematic review - Thalhah Bin Isman; Armanto Makmun; Nikmawati Nikmawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hypertension is one of the most prevalent non-communicable diseases and a major risk factor for cardiovascular complications. Most individuals with hypertension are asymptomatic, and is therefore commonly described as a silent killer. Clean and Healthy Living Behavior (PHBS) is a promotive and preventive approach that plays an important role of Clean and Healthy Living Behavior (PHBS) in hypertension prevention and control. Purpose: To identify the role of Clean and Healthy Living Behavior (PHBS) in the prevention and control of hypertension based on evidence from previous studies. Method: A systematic review method by searching scientific articles from bibliographic sources including Google Scholar, PubMed, ResearchGate, Elsevier, and NCBI. The article selection process was conducted systematically through identification, screening, eligibility assessment, and narrative synthesis. A total of 15 relevant articles published between 2019 and 2026 were included in the review. Results: The findings indicated that the implementation of PHBS, including healthy dietary patterns, salt intake restriction, regular physical activity, smoking cessation, weight management, stress control, routine health examinations, and medication adherence, was associated with lower hypertension risk and better blood pressure control. Furthermore, health education, PHBS promotion, and community-based interventions contributed to improving knowledge, attitudes, and healthy lifestyle practices among the community, thereby reducing the risk of cardiovascular complications. Conclusion: Clean and Healthy Living Behavior (PHBS) is potentially important non-pharmacological strategy for both preventing hypertension and achieving long-term blood pressure control. Integrating PHBS into primary healthcare systems significantly lowers the risk of cardiovascular complications. Suggestion: Multidisciplinary collaboration, community empowerment, and sustainable health promotion strategies should be strengthened within primary care. Additionally, future research utilizing longitudinal and interventional designs is required to assess the long-term efficacy of PHBS programs across diverse populations.